Feasibility and preliminary outcomes of a mobile intervention combining cognitive behavioral therapy, virtual coaching, and nicotine replacement therapy for nicotine vaping cessation - Webb,J; Lin,Y-T; Ang,A; Michero,D; Majeed,A; Eisingerich,A; Glasner,S (Telemedicine Reports, 2023)
BACKGROUND: Despite research demonstrating that those who use e-cigarettes, also known as vaping, express an interest in quitting, evidence-based vaping cessation interventions are lacking. The purpose of this study was to examine the feasibility and preliminary outcomes of an mHealth vaping cessation intervention. METHODS: Adults (N = 51) who were vaping nicotine were recruited online and enrolled in a 6-week mHealth intervention combining nicotine replacement therapy (NRT), self-guided cognitive behavioral therapy (CBT), and coaching support through telephone and asynchronous messaging. Feasibility and self-reported 7- and 30-day abstinence were assessed at baseline and 1-month postquit date. RESULTS: The majority of participants completed treatment (45/51) and found the intervention helpful in supporting their vaping behavior change objectives. At 1-month postquit date, 48.9% (22/45) of study completers reported 7-day point prevalence abstinence and 28.8% (13/45) reported continuous 30-day abstinence. CONCLUSIONS: Findings provide preliminary support for an mHealth intervention approach to vaping cessation combining remote CBT-based coaching with NRT.